Analysis of step kinematics during maximum speed of 60 m sprint performance - Rafał Omelko; Marek Fostiak; Krzysztof Mackala (Kazimierz Wielki University, 2018)
The purpose of this study was to examine the step kinematics variables (step length, step frequency, ground contact time, flight time, and step velocity) of maximum speed measured during 60 m sprint performance from starting block. Two groups of seven fast (best 100-m time: 10.37 ± 0.04 s) and seven sub-fast (best 100-m time: 10.71 ± 0.15 s) sprinters were recruited. Step kinematics were extracted from the first nine running steps of the 20-m sprint (between 40-60 m) of 60 m sprint performance form the block using the Opto-Jump-Microgate system (Opto Jump, Italy). It can be clearly seen that the average time of the flight phase, the frequency and length of the step showed significant statistical differences between the groups. Our experiment did not show significant changes in CT and FT in either group of sprinters and showed a relatively linear course from step two to step eight . The velocity of step execution in the fast sprinters showed a linear increase across steps one to nine however no changes in SL between step four and seven was noticed when compared with earlier steps three and six. In turn, the sub-fast sprinters showed more pronounced variation in SV and SL, which may explain the slower running velocity in this group of sprinters. Analysis of the obtained results may be of great importance for coaches. In order to reach a higher value of maximal sprinting speed the optimal interaction between each variables is noteworthy.